2018
DOI: 10.1002/ejp.1292
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided adductor canal block after arthroscopic anterior cruciate ligament reconstruction: Effect of adding dexamethasone to bupivacaine, a randomized controlled trial

Abstract: Adding dexamethasone to bupivacaine in adductor canal block significantly increases the duration of sensory block, time to first analgesic requirement and patients' satisfaction score in anterior cruciate ligament arthroscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
(42 reference statements)
3
20
0
Order By: Relevance
“…The results of this study confirm the efficacy of dexamethasone in prolonging the analgesic effect of bupivacain in the axillary block for upper limb surgery. Thus our investigation finds the result of several previous studies [5][6][7]. However, in these previous studies the results are variable ranging from 30 to 80% any route of administration confused, peri or intravenous.…”
Section: Discussionsupporting
confidence: 72%
“…The results of this study confirm the efficacy of dexamethasone in prolonging the analgesic effect of bupivacain in the axillary block for upper limb surgery. Thus our investigation finds the result of several previous studies [5][6][7]. However, in these previous studies the results are variable ranging from 30 to 80% any route of administration confused, peri or intravenous.…”
Section: Discussionsupporting
confidence: 72%
“…Its perineural mechanism, although likely multifactorial, may stem from its anti-inflammatory actions [ 10 ]. Dexamethasone was proven to prolong the duration of an ACB when compared to control (bupivacaine only) and decrease opioid consumption [ 11 ]. Few studies have utilized the combination of Dex-Dex.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Ibrahim et al (2019) in a recent issue of the journal. The authors performed a randomized clinical trial in 60 patients undergoing arthroscopic anterior cruciate ligament reconstruction and concluded that the addition of dexamethasone to bupivacaine in adductor canal block provides prolonged post-operative analgesia and less post-operative analgesic consumption than bupivacaine alone.…”
Section: Comment On a Paper By Ibrahim Et Al Entitledmentioning
confidence: 99%